Estudo da Suplementação Oral com Cúrcuma (Curcuma longa L.) Associada ao Exercício Resistido de Subida em Escada no Músculo Extensor Longo dos Dedos de Ratos em um Modelo de Artrite Reumatoide - Kuhn, Mikael Gerson (2024)
Rheumatoid arthritis (RA) is a condition resulting from a systemic autoimmune disease that can cause tissue damage, including muscular tissue. The conventional treatment for RA, involving the use of medications, may lead to side effects such as dependency, depression, and gastrointestinal alterations like digestive bleeding and peptic ulcers. For this reason, the search for complementary treatments is essential. The antiinflammatory characteristic of turmeric (Curcuma longa L.) makes it an option for RA treatment. On the other hand, studies have explored the benefits of resistance exercise as a complementary treatment for RA. Therefore, the aim of this study was to evaluate the morphological and functional effects of turmeric associated with resistance stair climbing exercise (RSCE) on the extensor digitorum longus (EDL) muscle in Wistar rats induced with RA. Thirty-one rats, aged three months and with an average weight of 340g, were divided into five groups: control group (CG) (n=6), RA group (RAG) (n=6), RA and turmeric group (RAGT) (n=6), RA and RSCE group (RAGRE) (n=6), and RA, turmeric, and RSCE group (RAGTRE) (n=7). RA was induced by the Complete Freund's Adjuvant (CFA) model. The rats underwent a protocol of five functional assessments to measure inflammation through joint edema, muscular strength through grip strength, joint disability with the time of paw elevation (TPE), and Von Frey nociception test. The animals' body weight was measured every week. Turmeric treatment was administered by gavage (100 mg/kg/day) for 14 consecutive days, while resistance exercise was performed by the RSCE model, with load progression (25%, 35%, and 50% of body weight) and fixed number of sets and repetitions (3 sets and 8 repetitions), for 14 alternate days. Euthanasia of the animals occurred on the 24th day of the experiment, 15 days after intra-articular induction. The EDL muscle was collected and processed for morphological and morphometric analysis of muscle fibers, connective tissue, and neuromuscular junctions (NMJs). A reduction in the Lee Index was observed in arthritic animals. RA caused joint edema, loss of muscle strength, increased TPE, and increased nociceptive threshold. Morphological and morphometric analyses indicated punctual alterations in muscle fibers due to RA, such as granulation tissue, amorphous fibers with dye difference, basophilic halo nuclei, centralized nuclei, and neuromuscular spindles with disorganized capsule and intrafusal fibers in degeneration, reduction in area and larger diameter of muscle fibers, and increased number of capillaries, however, these changes were less expressive in groups treated with RSCE. The NMJs of RAG presented an increase in the smaller diameter; however, this parameter was reversed by RSCE. In conclusion, RA, through functional assessments, caused damage to the animals' motor function, but was mitigated by RSCE. Morphological and morphometric analyses indicated degenerative alterations in muscle fibers due to RA, but these were attenuated by RSCE, both alone and associated with turmeric supplementation. In the parameters used, turmeric alone did not reverse the changes resulting from RA.